(untitled) (Revista Lusófona de Educação, 2025)
Teacher professional development within the context of learning communities is a central theme in Inclusive Education, highlighting the need to deepen the role of these communities in the sharing of strategies, critical reflection, and co-construction of inclusive practices. Therefore, our objective is to identify teachers’ perspectives on the challenges and opportunities for learning and professional development in the workplace, and to characterise their experiences of participation in such communities. This descriptive-correlational quantitative study involved the administration of an online questionnaire to 102 professionals aged between 31 and 65 years (50.8±10.2), from preschool, primary and secondary education, 79 of whom were female. Internal consistency was confirmed (α=.96), and the exploratory factor analysis indicated a four-factor solution explaining 46% of the total variance. The results show that teachers value continuous professional development for personal growth and improvement of pedagogical practices; they recognise the importance of school leadership and collaborative culture in fostering their professional development; and they see participation in learning communities as key to promoting equitable practices. The effective implementation of such communities in schools depends on the creation of support structures, effective leadership, and a culture focused on lifelong learning that promotes professional development. Keywords: Learning Communities; Collaborative Culture; Teacher Professional Development; Inclusive Education; Inclusive Pedagogical Practices